Characteristics of Laryngomalacia Patients at Department of Otorhinolaryngology-Head and Neck Surgery Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia Period 2021-2022 - Toer, Fatharani Azka; Puspa Zuleika; Adelien; Lisa Apri Yanti; Fiona Widyasari (HM Publisher, 2023)
Laryngomalacia is a congenital laryngeal disorder that is commonly found as a cause of stridor in infants and children. This disorder causes the collapse of the structures in the larynx resulting in impaired breathing and eating conditions in patients. This study aimed to present the characteristics of laryngomalacia patients at the Department of Otorhinolaryngology-Head and Neck Surgery (ORL-HNS) Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia, period 2021-2022. This was a descriptive observational study that used medical record data as secondary data and primary data in the form of questionnaires in the medical record section and ORL-HNS at Dr. Mohammad Hoesin General Hospital, Palembang, period 2021-2022. Data evaluated included age, gender, clinical symptoms, classification based on Olney distribution, degree of severity, comorbid factors, and therapy. This study showed that most patients were in the age group 3-12 months (52.9%). More were found in males (73.5%). The most common clinical symptoms were eating disorders (51.4%). The most common classification is type 1 (52.9%). Most patients come with a mild degree of severity (61.8%). The most common comorbid factors were neurological diseases (35.1%). The type of medical therapy was given to the majority of patients (94.1%).